Determination of Retinol, alpha-Tocopherol, Lycopene, and beta-Carotene in Human Plasma Using HPLC with UV-Vis Detection: Application to a Clinical Study - Kanďár Roman; Novotná Pavla; Drábková Petra (Hindawi Publishing Corporation, 2013)
A method is described here for the simultaneous determination of retinol, alpha-tocopherol, lycopene, and beta-carotene in human plasma. The effectiveness of various protein precipitants and extraction solvents was tested. After adequate sample preparation, the samples were injected directed into the HPLC system. The separation was realized on analytical reversed-phase column with a UV-Vis detection. The analytical performance of this method was satisfactory. The intraassay and interaassay coefficients of variation were below 10%. The recoveries were as follows. 97.0% (CV 2.4%) for retinol, 94.6% (CV 1.7%) for alpha-tocopherol, 91.9% (CV 3.6%) for lycopene, and 93.9% (CV 4.2%) for beta-carotene. The levels of selected fat-soluble vitamins in plasma of patients with cardiovascular disease were measured and discussed.
Stanovení retinolu, alfa-tokoferolu, lykopenu a beta-karotenu v lidské plazmě metodou HPLC s UV-Vis detekcí: Aplikace pro klinickou studii
Keywords: performance liquid-chromatography; intima-media thickness; electrochemical detection; phase hplc; serum; antioxidant; risk; tocotrienols; biomarkers; disease; vitamíny rozpustné v tucích; kapalinová chromatografie; pacienti s kardiovaskulárním onemocněním